Predictors of the Health-Seeking Behavior of Predominantly Christian and Muslim Communities in Lanao del Norte - 0. TAN, BERNADETTE; A. ROSCOM, BRIGIDA (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)